1916 Miss. Laws 388-89 - (:unkn) unknown (My University, 1916)
Ch. 245 § 14(d): It shall be unlawful for any body of men whatsoever, other than the regularly organized land and naval militia of this state, the land and naval forces of the United States, and the students of public or of regularly chartered educational institutions where military science is a prescribed part of the course of instruction, to associate themselves together as a military organization for drill or parade in public with firearms in this state, without special license from the governor for each occasion
Keywords: MILITIAS